Penerapan Model Pembelajaran Complete Sentence Dalam Meningkatkan Keterampilan Menulis Paragraf Pada Mata Pelajaran Bahasa Indonesia - A.Taufik Asmur; Andi Sukri Syamsuri; Anin Asnidar (STIKes Ibnu Sina Ajibarang, 2024)
The main problem in this research is how to apply the complete sentence learning model in improving paragraph writing skills in Indonesian language subjects for class V students at SD Negeri 37 Palambarae. This research aims to determine the application of the complete sentence learning model in improving paragraph writing skills in Indonesian language subjects for class V students at SD Negeri 37 Palambarae. The type of research used is classroom action research which consists of two cycles where each cycle is carried out in 2 meetings. This research procedure consists of 4 stages in each cycle, namely planning, implementing actions, observing and reflecting. The subjects in this research were 21 fifth grade students at SD Negeri 37 Palambarae. The results of this research show that in cycle I of the 21 students who completed individually, only 12 or around 57.14% met the Minimum Completeness Criteria. Meanwhile, in cycle II, out of 21 students, 19 students or 90.47% had fulfilled the KKM and classically had been fulfilled, namely the average score obtained was 80.19 or was in the high category. Based on the results of the research above, it can be concluded that the complete sentence model can improve paragraph writing skills in class V Indonesian language subjects at SD Negeri 37 Palambarae.